Serial and parallel resource-constrained projekt scheduling methodes revisited: Theory and computation - Rainer Kolisch (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
We consider the classical resource-constrained project scheduling problem (RCPSP). The paper gives a detailed algorithmic description and provides theoretical results on two widely known problem specific heuristics: The serial and the parallel scheduling scheme. An in-depth computational study compares both schemes when applied as a deterministic single-pass and a probabilistic multi-pass (sampling) method.
Keywords: 650; Resource-Constrained Project Scheduling; Serial And Parallel Scheduling Method; Single-Pass And Multi-Pass Heuristics; Sampling; Active And Non-Delay Schedules; Priority Rules; Experimental Investigation; Projektmanagement; Theorie